Medication compliance by cat owners prescribed treatment for home administration. - Odom TF; Riley CB; Benschop J; Hill KE (Wiley Periodicals LLC on behalf of American College of Veterinary Internal Medicine., 2025)
BACKGROUND: Most veterinary literature examining medication compliance has described the phenomenon in dogs. The evidence available regarding factors affecting cat owner medication compliance is limited. OBJECTIVES: Identify and describe factors associated with cat owners' noncompliance with veterinary recommendations for pet medications, as well as client-reported barriers and aids to administering medications prescribed by primary care veterinarians. SUBJECTS: Cat owners presenting their animals for veterinary examination and treatment. METHODS: A cross-sectional survey of cat owners' compliance with veterinary medication recommendations was performed from January 9, 2019, to July 18, 2020. A convenience sample of owners prescribed medication for their pets by veterinarians during or after elective veterinary examination was recruited to respond to questions regarding medication administration experience and compliance. Follow-up was obtained from owners to determine if the course of medication had been completed. Compliance data were analyzed descriptively, and logistic regression was performed. RESULTS: Medication noncompliance was recorded for 39% (26/66) of cat owners. A quarter (16/66) reported challenges in administering medication to their pets; the most commonly cited reason was a resistant pet. Oral administration of antibiotics was significantly associated with noncompliance (P = .01). Clients with limited pet ownership experience were less likely to be noncompliant (P = .04). CONCLUSIONS AND CLINICAL IMPORTANCE: Clients' inability to medicate their cats PO may have implications for clinical outcomes and antimicrobial stewardship. Alternatives to direct PO administration of solid-form medications in cats should be considered. Demonstrating administration techniques to all clients may improve compliance and influence clinical outcome.
Keywords: antibiotics; antimicrobials; oral; palatability; Cats; Animals; Cross-Sectional Studies; Medication Adherence; Cat Diseases; Humans; Female; Male; Surveys and Questionnaires; Ownership; Veterinary Drugs; Anti-Bacterial Agents